PENGARUH TEKNIK MESSAGE TERHADAP PENGURANGAN NYERI PERSALINAN KALA 1 FASE AKTIF DI PUSKESMAS BILOKKA KABUPATEN SIDRAP TAHUN 2021 - Umi Kalsum; Hasrida H; Jusmawati J; Dwi Ghita (An Idea Health Journal, 2021)
The purpose of this study was to describe the effect of massage techniques on reducing labor pain in the active phase of the 1st stage of labor at the Bilokka Health Center, Sidrap Regency. Pain during labor increases maternal anxiety which increases the risk of prolonged labor and the high rate of cesarean sections. Because this is a determining point whether a mother in labor can undergo a normal delivery or end with an action due to the presence of a sore that causes very severe pain, it is very important to help childbirth meet the mother's need for security and comfort. One of the efforts to reduce labor pain is the massage technique.This study used a pre-experimental research method with a one group pretest posttest research design. Samples were taken using a purposive sampling technique, as many as 20 mothers gave birth. The instrument used in this study was an observation sheet. The data were analyzed by two kinds of bivariate analysis techniques using the SPSS 24 program. Before implementing the massege technique, most of the respondents were on a scale of 406 (moderate pain) as many as 11 people (55%). After doing the massage technique, most of the respondents were on a scale of 4-6 (mild pain) as many as 14 people (70%). The results of the t-test obtained a significant value (0.000 <0.05) meaning Ho is rejected and Ha is accepted. So it can be concluded that there is an effect of massage technique on reducing labor pain in the active phase of the 1st stage at the Bilokka Public Health Center, Sidrap Regency.